3D-printing of architectured short carbon fiber-geopolymer composite. (1st December 2021) - Ma, Siqi; Yang, Hualong; Zhao, Shenjian; He, Peigang; Zhang, Zuhua; Duan, Xiaoming; Yang, Zhihua; Jia, Dechang; Zhou, Yu
Abstract: Developing advanced lightweight structures with both high strength and high toughness remains challenging. Herein, we provide a combined experimental and simulation method to fabricate 3D-printed geopolymer complex structures with lightweight, high strength and superior toughness for the first time. In this research, short carbon fiber reinforced geopolymer (Csf GP) composites were printed using 3D printing technology, and the rheological properties of Csf GP inks and the mechanical properties of hardened geopolymer composite structures were systematically studied. The Csf GP inks exhibited obvious shear-thinning behavior, which facilitated ink-extrusion from a micro-nozzle, conserving the filamentary shape and supporting the subsequent printed layers. In Csf GP composites, the consistent orientation distribution of short carbon fibers primarily enhanced their mechanical properties. When fiber content was 3 wt %, flexural strength and compressive strength of the Csf GP composite were 309.2% and 375.8% higher than those of nonreinforced geopolymer, respectively. Subsequently, Csf GP composites of the Bouligand architectures were successfully 3D-printed, and they showed superior load-bearing capacity and non-brittle failure mode due to their hierarchically ordered architectures and sophisticated interfaces. 3D printing together with Bouligand-structure designing provide a novel approach for the Csf GP composites of lightweight, high strength and superior toughness, which would lead to a resurgence of interest in new lightweight structure design and manufacturing strategies. Graphical abstract: Image 1 Highlights: Short carbon fiber reinforced geopolymer (Csf GP) inks were 3D printed by direct ink writing. Consistent fiber orientation distribution was achieved in the printed Csf GP composites. Csf GP of Bouligand structures were designed and printed, and the fracture behavior of these structures was investigated. The obtained Csf GP of Bouligand structures showed light-weight, high strength and superior toughness, and non-brittle failure behavior.